PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI TERHADAP KINERJA DOSEN DENGAN DISIPLIN SEBAGAI VARIABEL MEDIASI ( Studi Dosen Politeknik Ilmu Pelayaran Semarang ) (Students' Journal of Economic and Management, 2013)
The purpose of this study is to examine the effect of professional competence and motivation on performance, moderated by the work discipline of  lecturer in Polytechnic State of Semarang. Based on that conditions, the title of this study is "The Effect of The Professional Competence and Work Motivation in The Lecturer Performance as Discipline of Mediating Variables (Empirical Study in the lecturer of Polytechnic State of Semarang)". The population of this study is 93 Lecturer of Polytechnic State of Semarang. Analysis of the data was using double linear regression. Based on this study that the professional competence does not affect in discipline of work, the motivation is affect in discipline of work, the professional competence does not affect the performance of lecturers, the motivation is effect on the performance of lectures, the disipline of work is effect on the performance of lecturer, the professional competence is mediate the discipline of work against the performance of lecturer because the indirect effect has great influence than the direct influence and discipline of work and the work motivation mediate the performance of lecturers for the indirect effect is smaller than the direct effect. Key words: Leadership, motivation, disipline of work and performance of lecturer